Network Analysis of the Integration Level of the Universities Participating in Project 5-100 in the International Higher Education Area - P. A. Zhdanov; N. A. Polikhina; E. Yu. Sema; L. V. Kazimirchik; I. B. Trostyanskaya; A. A. Barsukov (Moscow Polytechnic University, 2019)
The paper analyzes measures adopted by the Russian Federation on internationalization and globalization of the higher education system, its integration into the international scientific and education area. One of the initiatives of the authorities of the Russian Federation in this direction is Project 5-100, designed to increase the competitiveness of both a selected group of universities and the Russian higher education system as a whole. Among the successful practices of Project 5-100, one can identify the presentation of a single stand of participating universities at the international education exhibitions APAIE, EAIE, NAFSA. Within this study, we explore the cooperation of the universities participating in Project 5-100 with potential international partners at global educational exhibitions by means of network analysis with graphs. The effectiveness of such cooperation from the point of view of integration of the universities from this group into the international higher education area is determined through estimations of the usefulness of participation in such events made by the universities and through scientometric analysis. As a result of this study, it was revealed that active participation in international educational exhibitions including negotiating, establishing contacts with international partners, contributes significantly to the promotion of the universities participating in Project 5-100 in the international arena.